Integration of Ethnopedagogy in the P5 Module Based on Besutan Art as a Medium for Preserving Jombang Culture - Anggraeni, Kiki Hapsari; Hendratno, Hendratno; Sukartiningsih, Wahyu (Journal of Innovation and Research in Primary Education, 2025)
This study aims to explore and develop a Pancasila Student Profile (P5) learning module based on Kesenian Besutan, a traditional art form from Jombang, through the integration of ethnopedagogical principles. Using a mixed methods approach, the research combines qualitative data from interviews with cultural practitioners, classroom observations, and document analysis with quantitative data from expert validation of the developed module. The goal is to preserve local culture while simultaneously cultivating students’ character in line with Pancasila values. The qualitative findings revealed that Besutan carries deep historical and philosophical meaning related to the Indonesian struggle for independence and local wisdom, making it a strong foundation for cultural-based learning. Quantitative validation from education experts and cultural figures resulted in an average score of 91.67, indicating the module is "highly feasible" for classroom implementation. The module encourages student engagement through contextual learning, collaborative projects, and critical reflection, structured in four main phases: introduction, contextualization, action, and reflection. This research contributes to the growing body of knowledge on ethnopedagogical-based curriculum development and highlights the potential of local art forms in promoting cultural literacy and civic responsibility. The study recommends broader trials and government support to integrate such culturally rich modules into primary education for sustainable cultural preservation and character building.